Bio-elastomer nanocomposites reinforced with surface-modified graphene oxide prepared via in situ coordination polymerization. Issue 60 (5th October 2020) - Bahena, Arely; Magaña, Ilse; López González, Héctor Ricardo; Handa, Rishab; Enríquez-Medrano, Francisco Javier; Kumar, Sugam; Carrizales, Ricardo Mendoza; Fernandez, Salvador; Valencia, Luis; Díaz de León Gómez, Ramón Enrique
Abstract : This article proposes a method to produce bio-elastomer nanocomposites, based on polyfarnesene or polymyrcene, reinforced with surface-modified graphene oxide (GO). Abstract : This article proposes a method to produce bio-elastomer nanocomposites, based on polyfarnesene or polymyrcene, reinforced with surface-modified graphene oxide (GO). The surface modification is performed by grafting alkylamines (octyl-, dodecyl-, and hexadecylamine) onto the surface of GO. The successful grafting was confirmed via spectroscopic (FTIR and Raman) and X-ray diffraction techniques. The estimated grafted amines appear to be around 30 wt%, as calculated via thermogravimetric analysis, increasing the inter-planar spacing among the nanosheets as a function of alkyl length in the amine. The resulting modified GOs were then used to prepare bio-elastomer nanocomposites via in situ coordination polymerization (using a ternary neodymium-based catalytic system), acting as reinforcing additives of polymyrcene and polyfarnesene. We demonstrated that the presence of the modified GO does not affect significantly the catalytic activity, nor the microstructure-control of the catalyst, which led to high cis -1, 4 content bio-elastomers (>95%). Moreover, we show via rheometry that the presence of the modified-GO expands the capacity of the elastomer to store deformation or applied stress, as well as exhibit an activation energy an order of magnitude higher.